Changes of vertical jump height in response to acute and repetitive fatiguing conditions - Kamandulis, S.; Venckunas, T.; Snieckus, A.; Nickus, E.; Stanislovaitiene, J.; Skurvydas, A. (Science & Sports, 2016)
Purpose: The purpose of the study was to assess value of jump height variation as an indicator of neuromuscular fatigue in response to three acute interventions: (1) incremental leg cycling until volitional exhaustion, (2) 70 drop jumps, (3) 24 hours sleeplessness; and (4) during 6-week period within a basketball competition season.